Proarrhythmic remodelling of the right ventricle in a porcine model of repaired tetralogy of Fallot. Issue 5 (8th October 2016) - Benoist, David; Dubes, Virginie; Roubertie, François; Gilbert, Stephen H; Charron, Sabine; Constantin, Marion; Elbes, Delphine; Vieillot, Delphine; Quesson, Bruno; Cochet, Hubert; Haïssaguerre, Michel; Rooryck, Caroline; et al.
Abstract : Objective: The growing adult population with surgically corrected tetralogy of Fallot (TOF) is at risk of arrhythmias and sudden cardiac death. We sought to investigate the contribution of right ventricular (RV) structural and electrophysiological remodelling to arrhythmia generation in a preclinical animal model of repaired TOF (rTOF). Methods and results: Pigs mimicking rTOF underwent cardiac MRI functional characterisation and presented with pulmonary regurgitation, RV hypertrophy, dilatation and dysfunction compared with Sham-operated animals (Sham). Optical mapping of rTOF RV-perfused wedges revealed a significant prolongation of RV activation time with slower conduction velocities and regions of conduction slowing well beyond the surgical scar. A reduced protein expression and lateralisation of Connexin-43 were identified in rTOF RVs. A remodelling of extracellular matrix-related gene expression and an increase in collagen content that correlated with prolonged RV activation time were also found in these animals. RV action potential duration (APD) was prolonged in the epicardial anterior region at early and late repolarisation level, thus contributing to a greater APD heterogeneity and to altered transmural and anteroposterior APD gradients in rTOF RVs. APD remodelling involved changes in Kv4.3 and MiRP1 expression. Spontaneous arrhythmias were more frequent in rTOF wedges and more complex in the anterior than in the posterior RV. Conclusion: Significant remodelling of RV conduction and repolarisation properties was found in pigs with rTOF. This remodelling generates a proarrhythmic substrate likely to facilitate re-entries and to contribute to sudden cardiac death in patients with rTOF.